Conservative Treatment of Third Trimester Appendicitis Misdiagnosed as Round Ligament Pain. A Case Report and Review of the Literature in a Resource-Limited Setting - Hassan RA; Ali IA; Elmi AH; Omar AA (International Journal of Women's Health)
Rayaan Abdirahman Hassan,1 Ismail A Ali,2 Abdullahi Hassan Elmi,3 Abdullahi Abdirahman Omar1 1Dr.Sumait Hospitals, Faculty of Medicine and Health Sciences, SIMAD University, Mogadishu, Somalia; 2Department of Surgery, Dr. Sumait Hospitals, Faculty of Medicine and Health Sciences, SIMAD University, Mogadishu, Somalia; 3Department of Nursing and Midwifery, Dr. Sumait Hospital, Faculty of Medicine and Health Sciences, SIMAD University, Mogadishu, SomaliaCorrespondence: Rayaan Abdirahman Hassan, Email rayaanabdirahmanh@simad.edu.soIntroduction: Identifying acute appendicitis during pregnancy is particularly challenging, especially in the third trimester, as its symptoms may resemble typical gestational discomfort. While surgery remains the standard treatment, conservative treatment is being considered more often, especially when surgical intervention can pose risks to either the mother or the fetus.Case Presentation: We report the case of a 30-year-old woman at 33 weeks of gestation who presented with right lower quadrant pain initially misattributed to round ligament strain. Her condition deteriorated over several days with worsening abdominal pain, fever, and leukocytosis. Imaging confirmed an acute uncomplicated appendicitis. After multidisciplinary evaluation and counseling, the patient declined surgery due to concerns over fetal safety. A conservative approach with intravenous antibiotics was initiated, resulting in complete clinical resolution. The patient delivered a healthy infant at term, without complications or recurrence.Conclusion: This case demonstrates that conservative management of appendicitis during the third trimester can be a safe and effective alternative for highly selected patients. This underscores the importance of individualized care, shared decision-making, and close clinical monitoring, particularly when standard surgical treatment has declined. As the conversation around non-operative strategies evolves, this case adds meaningful support for expanding tailored management options during pregnancy in resource-limited settings.Keywords: appendicitis in pregnancy, conservative management, third trimester, round ligament pain, non-operative treatment, maternal-fetal safety